The Prospects for the Development of Souraja Cultural Heritage Area for Community-Based Tourism Development, Palu City - Harifuddin Thahir; Irdinal Arief; Noor Riefma Hidayah; Suci Amalia Namira (The Journal Publishing, 2023)
Community-based tourism can create employment opportunities for local communities and reduce poverty, were tourism revenues from tourism service. In the development of facilities and infrastructure needed by the development prospects, apart from being a tourist object, the community plays a role in its development and is integrated with the surrounding environment. The thing of tourism is in the form of cultural heritage buildings located in urban areas so that this becomes integrated with the local community and the Government. This happened in Palu City, but a natural disaster (earthquake, liquefaction and tsunami) occurred on 2018 which resulted in damage some buildings, one of which was the Souraja traditional house located in Kampung Lere, Palu. The